Strategi komunikasi komunitas manusaya dalam melaksanakan program sosial: Studi Kasus Program Sosial Titik Balik dan Kelas Pemenang - Lie, Valerie; Primadini, Intan (Universitas Dr.Soetomo, 2021)
All things about the lack of humanity are proven by violence cases and negative stigma in the society. The research aims to find out and analyze communication strategy applied to Manusaya in the effort to #MemanusiakanManusia through their social proggrame. Concept in this research reffering to Planning and Management concept by Cutlip, Center, and Broom that has stages Defining PR Problems, Planning and Programming, Taking Action and Communicating, and Evaluating the Program. This qualitative descriptive research used study case method. Primary data obtained by researchers is through in-depth interviews with four persons who responsible to be a interviewees. The result of this research shows that the strategy and tactic that Manusaya used was already following the concept. The campaign used online media and collaborated with external communities in the development of the program. The evaluation is carried out through two stages routine evaluation and whole evaluation. The suggestion of this research is that communication by Manusaya could be more varied and ensure the information can be understood properly by stakeholders.Keyword: Campaign; Communications Strategy; Social Proggrame.